2010
DOI: 10.5114/jcb.2010.14402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigations Effectiveness of two different HDR brachytherapy regimens with the same BED value in cervical cancer

Abstract: PurposeTo analyze the effectiveness of biologically effective dose (BED) in two different regimens of HDR brachytherapy keeping the same total BED to point A and to compare the relationship of overall treatment time in terms of local control and bladder and rectal complications.Material and methodsThe study included two groups comprising a total of 90 cervical cancer patients who underwent external beam radiotherapy (EBRT) followed by HDR intracavitary brachytherapy (ICBT). EBRT treatment was delivered by a Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Novetsky et al reported a 5-year PFS of 75% in a trial of 77 patients treated with EBRT and ICR with 9 Gy per fraction for 2 fractions [ 13 ]. Passi et al, reported a 6-month local recurrence of 3.2% in patients who received ICR with 9.5 Gy × 2 fractions compared to 5.4% in patients who received 7.5 Gy per fraction [ 14 ]. In a trial of 604 patients, Hendry et al found that patients who got 9 Gy × 2 fractions had a 5-year local control rate of 82 percent and patients who received 7 Gy × 4 fractions had a 5-year local control rate of 89 percent (p = 0.72) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novetsky et al reported a 5-year PFS of 75% in a trial of 77 patients treated with EBRT and ICR with 9 Gy per fraction for 2 fractions [ 13 ]. Passi et al, reported a 6-month local recurrence of 3.2% in patients who received ICR with 9.5 Gy × 2 fractions compared to 5.4% in patients who received 7.5 Gy per fraction [ 14 ]. In a trial of 604 patients, Hendry et al found that patients who got 9 Gy × 2 fractions had a 5-year local control rate of 82 percent and patients who received 7 Gy × 4 fractions had a 5-year local control rate of 89 percent (p = 0.72) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The institutional protocol utilized a dose fraction of 7.5 Gy, while a dose fraction of 9 Gy was selected based on the findings of multiple studies available in the literature which a demonstrated comparable to superior local control with higher doses per fractionation, despite a reduction in the overall dose of brachytherapy administered [8,[10][11][12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…At the end of 6 months 90% and 86.7% patients of both treatment group achieved complete response. Passi et al in their study found 80% and 85% complete response using HDR brachytherapy of 9.5 Gy in two fractions and 7.5 Gy in three fractions 11 . No difference in local control, disease free survival and toxicities had been found in the study of Patel et al (2011) where comparison done between 9 Gy per fraction in two fractions & 6.8 Gy per fraction in 3 fractions in 104 patients of stages IIB and IIIB of cervical carcinoma who were treated with EBRT and HDR ICBT 12 .…”
Section: Patient Characteristicsmentioning
confidence: 94%
“…The high dose rate intracavitary brachytherapy in a higher number of insertions with smaller doses per insertion is associated with higher radiobiological effects and reduced toxicity. 6 The aim of this study was to compare the toxicity outcome of concurrent teletherapy and brachytherapy with teletherapy followed by brachytherapy using two different fractionation schedules in locally advanced cervical carcinoma (stage IIB-IVA).…”
Section: Introductionmentioning
confidence: 99%